2000
DOI: 10.1053/jhep.2000.8532
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic cytochrome P450 down-regulation during aseptic inflammation in the mouse is interleukin 6 dependent

Abstract: Expression of cytochromes P450 (CYP) is markedly reduced during inflammatory processes. In vitro studies with hepatocytes have shown that cytokines generated during these processes down-regulate CYP. However, it is not clear to what extent each individual cytokine contributes to the overall reduced expression of the various CYP isoenzymes in vivo. Interleukin 6 (IL-6), a major player during inflammatory processes, is recognized as the most important cytokine modulating the hepatic expression of acute-phase pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
98
1
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(109 citation statements)
references
References 34 publications
(51 reference statements)
8
98
1
2
Order By: Relevance
“…This represents a widespread repression of drug transport within the liver with transporters mediating both uptake and efflux from the affected hepatocyte. These findings are consistent with previously reported in vitro and in vivo models of acute inflammation in which IL-6 is reported to be the major contributor to the repression of hepatic transporter mRNA expression (Siewert et al, 2000;Hartmann et al, 2001;Teng and Piquette-Miller, 2005). The mRNA expression of Mdr1a was not anticipated to be reduced, based on the findings of previous studies that report the importance of post-translational factors in Mdr1a expression (Cornwell, 1991).…”
Section: Downregulation Of Hepatic Metabolism In Malignancysupporting
confidence: 92%
See 1 more Smart Citation
“…This represents a widespread repression of drug transport within the liver with transporters mediating both uptake and efflux from the affected hepatocyte. These findings are consistent with previously reported in vitro and in vivo models of acute inflammation in which IL-6 is reported to be the major contributor to the repression of hepatic transporter mRNA expression (Siewert et al, 2000;Hartmann et al, 2001;Teng and Piquette-Miller, 2005). The mRNA expression of Mdr1a was not anticipated to be reduced, based on the findings of previous studies that report the importance of post-translational factors in Mdr1a expression (Cornwell, 1991).…”
Section: Downregulation Of Hepatic Metabolism In Malignancysupporting
confidence: 92%
“…On administration of these cytokines to rodents, reproducible reductions of Cyp3a mRNA expression with IL-1b, TNF-a and especially IL-6 were observed (Ghezzi et al, 1986a, b;Ferrari et al, 1993). Furthermore, in in vivo studies in IL-6-deficient mice, no repression in Cyp3a11 was seen on treatment with turpentine or tuberculosis vaccine (Siewert et al, 2000). Moreover, deletion of the IL-1b and TNF-a receptors in vivo had little or no effect on Cyp3a11 downregulation (Ashino et al, 2004).…”
Section: Discussionmentioning
confidence: 98%
“…In particular, because many cytokines are involved in the regulation of CYP genes, and because the cytokines affect each other's expression, it is very difficult to determine which cytokine(s) regulates the expression of which CYP gene. 17) In the present study, we paid considerable attention to the inflammatory cytokines TNFα and IL-1β, because they can downregulate the expression of multiple CYP genes, [13][14][15][16] suggesting that they could be key regulators of this process. Therefore, we assessed the TNFα and IL-1β mRNA levels in mice treated with LPS plus PCN, TCPOBOP, or B(a)P. In spite of the presence of CYP inducers, LPS treatment resulted in significant increases in the TNFα and IL-1β mRNAs (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12] Other studies showed that the expression of these cytokines is correlated with changes in CYP gene expression and CYP enzymatic activities, during infection and inflammation. [13][14][15][16] In most of these studies, a decrease in CYP protein expression was succeeded or accompanied by a decrease in its mRNA, implicating transcription regulation as a primary mechanism. 17) These findings also underscore the importance of understanding the transcriptional mechanisms of the CYPs.…”
mentioning
confidence: 99%
“…Several studies [21,22] have revealed that a SFS liver graft retained the capacity to regenerate faster by modulation of the expression pattern of HGF, IL-6 and TGF-βl immediately after LDLT and both the regeneration rates and the levels of cytokines and growth factors were higher in SFS liver grafts than normal sized liver grafts. These markers have also shown an ability to decrease cytochrome P450 3A activity in the liver in both mice and humans [23][24][25] , which may decrease its ability to metabolize drugs. In other words, there were many more cytokines and growth factors (such as HGF, IL-6) in SFS liver grafts, which could decrease the clearance of tacrolimus.…”
Section: Discussionmentioning
confidence: 99%